2018
DOI: 10.3389/fvets.2018.00298
|View full text |Cite
|
Sign up to set email alerts
|

TB Control in Humans and Animals in South Africa: A Perspective on Problems and Successes

Abstract: Mycobacterium tuberculosis (M. tb) remains one of the most globally serious infectious agents for human morbidity and mortality, but with significant differences in prevalence across the globe. In many countries, the incidence is now low and declining, but control and eradication remain a distant view. Similarly, the prevalence of bovine TB caused by Mycobacterium bovis (M. bovis), varies significantly across regions, although unlike for M. tuberculosis, data are sparse. The reduction in incidence and prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…This is supported by other studies from Nigeria, calling for improved public communication around TB [65] , [66] , [67] . Mass awareness campaigns have been used sucesfully in South Africa and other settings to create awareness, reduce stigma, and improve case finding [56] , [68] , [69] . Improving accessibility to healthcare facilities with TB testing and treatment could include active case-finding, mobile TB clinics and working with the private sectors to ensure adequate support for referring TB patients for appropriate testing.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by other studies from Nigeria, calling for improved public communication around TB [65] , [66] , [67] . Mass awareness campaigns have been used sucesfully in South Africa and other settings to create awareness, reduce stigma, and improve case finding [56] , [68] , [69] . Improving accessibility to healthcare facilities with TB testing and treatment could include active case-finding, mobile TB clinics and working with the private sectors to ensure adequate support for referring TB patients for appropriate testing.…”
Section: Discussionmentioning
confidence: 99%
“…Many European Union countries also were successful to be recognized as officially TB free countries (27). However, BTB control is not practically feasible in low and middle income countries like Ethiopia through test and slaughter method alone due to lack of resources for rigorous testing, tracing, slaughtering of large number of positive cattle, and compensations to farmers (28).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the study highlighted the challenges involved in bovine tuberculosis control and the need for consideration of technical and social aspects for effective disease control (Borja et al 2018 ). In another study, Meiring et al ( 2018 ) used the implemented strategies employed for human TB control in South Africa as an example to explain and compare the feasibility of applying these strategies in bovine tuberculosis control. The authors explained that the mitigation of human TB incidence in this high burden country has been accomplished by increasing awareness of tuberculosis in public and antimicrobial therapy where both elements are lacking for bovine tuberculosis.…”
Section: Tackling M Bovis Infection At Human–animmentioning
confidence: 99%
“…The authors addressed a number of determinants such as lack of movement restrictions and proper monitoring of animals, inadequacy of veterinary resources and mandatory testing program or bovine tuberculosis, point-of-care diagnostic testing for cattle and the prevalence of bovine tuberculosis in wildlife may be responsible for the persistence of disease. The authors suggested that multisector collaborations are much needed to control bovine tuberculosis (Meiring et al 2018 ).…”
Section: Tackling M Bovis Infection At Human–animmentioning
confidence: 99%